Solid-state hydrolysis of postconsumer polyethylene terephthalate after plasma treatment - Mancini, Sandro Donnini [UNESP]; Nogueira, Alex Rodrigues [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Cruz, Nilson Cristino da [UNESP] (Wiley, 2013)
Plasma treatments were applied on the surface of postconsumer polyethylene terephthalate (PET) bottles to increase their wettability and hasten the subsequent hydrolysis process. Sixty-four treatments were tested by varying plasma composition (oxygen and air), power (25-130 W), pressure (50-200 mTorr), and time (1 and 5 min). The best treatment was the one applied in air plasma at 130 W and 50 mTorr for 5 min, as it provided the lowest contact angle, 9.4°. Samples of PET before and after the optimized plasma condition were subjected to hydrolysis at 205°C. Although the treatment changed only a thin surface layer, its influence was evident up to relatively high conversion rates, as the treated samples presented more than 40% higher conversion rates than the untreated ones after 2 h of reaction. Infrared spectroscopy showed that the terephthalic acid obtained from 99% of depolymerization was similar to the commercial product used in PET synthesis. © 2012 Wiley Periodicals, Inc.
Keywords: plasma treatment; polyesters; recycling; surface modification; Air plasmas; Commercial products; Conversion rates; High conversions; Plasma composition; Plasma conditions; Plasma treatment; Subsequent hydrolysis; Terephthalic acids; Thin surface layer; Contact angle; Infrared spectroscopy; Plasma applications; Polyesters; Polyethylene terephthalates; Reaction rates; Recycling; Surface treatment; Synthesis (chemical); Hydrolysis